Severe but Not Moderate Vitamin B12 Deficiency Impairs Lipid Profile, Induces Adiposity, and Leads to Adverse Gestational Outcome in Female C57BL/6 Mice - Ghosh, Shampa; Sinha, Jitendra Kumar; Putcha, Uday Kumar; Raghunath, Manchala (Frontiers in Nutrition, 2016)
Vitamin B12 deficiency is widely prevalent in women of childbearing age especially in developing countries. In the present study, through dietary restriction, we have established mouse models of severe and moderate vitamin B12 deficiencies to elucidate the impact on body composition, biochemical parameters and reproductive performance. Female weanling C57BL/6 mice were fed for four weeks, (a) control AIN-76A diet, (b) vitamin B12 restricted AIN-76A diet with pectin as dietary fiber (severe deficiency group, as pectin inhibits vitamin B12 absorption) or (c) vitamin B12 restricted AIN-76A diet with cellulose as dietary fiber (moderate deficiency group as cellulose does not interfere with vitamin B12 absorption). After confirming deficiency, the mice were mated with male colony mice and maintained on their respective diets throughout pregnancy, lactation and thereafter till 12 weeks. Severe vitamin B12 deficiency increased body fat % significantly, induced adiposity and altered lipid profile. Pregnant dams of both the deficient groups developed anemia. Severe vitamin B12 deficiency decreased the percentage of conception and litter size, pups were small-for-gestational-age and had significantly lower body weight at birth as well as weaning. Most of the offspring born to severely deficient dams died within 24 hours of birth. Stress markers and adipocytokines were elevated in severe deficiency with concomitant decrease in antioxidant defense. The results show that severe but not moderate vitamin B12 restriction had profound impact on the physiology of C57BL/6 mice. Oxidative and corticosteroid stress, inflammation and poor antioxidant defense seem to be the probable underlying mechanisms mediating the deleterious effects.